21st International Conference on Service-Oriented Computing (ICSOC).http://www.wikicfp.com/cfp/servlet/event.showcfp?eventid=176053&copyownerid=94289 - Andreou, Andreas S. (My University, 2026)
Organization and co-charing of the 19th International Workshop on Engineering Service-Oriented Applications and Cloud Services (WESOACS 2023) which was held in the context of the 21st International Conference on Service-Oriented Computing (ICSOC), November 28th – December 1st, 2023, Rome, Italy